2022
DOI: 10.1001/jamanetworkopen.2022.36914
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Standard-of-Care Practices Among Physicians Who Treat Other Physicians

Abstract: ImportanceEthical discussions have suggested that physicians who treat other physicians may put their physician-patients at risk of receiving non–standard-of-care treatment, which may result in worse outcomes. This phenomenon occurs when a physician treats a fellow physician as a VIP (very important person), and is therefore known as VIP syndrome. It is important to assess physicians’ perceptions when treating physician-patients.ObjectiveTo determine whether the physicians treating other physicians have attitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 17 publications
(48 reference statements)
0
0
0
Order By: Relevance
“… 5 , 32 , 37 , 38 First noted by Rhodes almost 40 years ago, this remains a concern in more recent literature. 23 The only quantitative study 18 found 42% of primary care doctors would order more tests and procedures, if their patient was another doctor, while a qualitative study 16 of oncology specialists found none reported differences in testing for their doctor–patients.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… 5 , 32 , 37 , 38 First noted by Rhodes almost 40 years ago, this remains a concern in more recent literature. 23 The only quantitative study 18 found 42% of primary care doctors would order more tests and procedures, if their patient was another doctor, while a qualitative study 16 of oncology specialists found none reported differences in testing for their doctor–patients.…”
Section: Resultsmentioning
confidence: 99%
“…Treating doctors can also experience frustration with their doctor–patients, if they felt they were being manipulated into a treatment plan against their better judgement. 16 , 31 , 33 As it can be time-consuming to treat a doctor–patient, the increased workload can also result in feelings of irritation. 26 , 27 , 32 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations